Alternative Fuels for Compression Ignition Engines (SpringerBriefs in Energy,, 2018)
This book examines the development and utilization of alternative fuels in order to reduce or control the environmental impact of internal combustion engine exhaust gases. Discussing alternative fuels such as dual fuel techniques, rubber seed/palm oil biodiesel, syngas dual-fuelling, water-in-diesel emulsions and gasification of date palm seeds, it is a valuable resource for researchers in the field of engine development and on alternative fuels.